Islamic Leadership Motivation in Muhammadiyah 3 Waru Junior High School - Anik Isticharoh (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
Leadership is defined as a dynamic principle impetus that motivates and coordinates used by institutions in completing or achieving goals. This reseearch uses descriptive method to explain data collection in the field, which provides an overview of the motivation of Islamic leadership obtained from observation. The approach in this study uses a qualitative approach. Data are written results from interviews in Mugaru Fest 2018 activities. Data sources are from teachers, vice principals, and principals. The results of this research appears in two kinds, positive motivation and inner-self motivation. The form of Islamic leadership motivation used in this research is a democratic model. There are several ways to increase the motivation of Islamic leadership as follows: respect, information, behavior, punishment, orders, and feelings.Keywords: Motivation, Leadership, Islamic, Islamic Thought, Teachers, Vice Principal, Principal, Junior HighSchool.